Gas sensing properties of multicomponent systems based on oxides of manganese, copper and yttrium - Yu. A. Stenkin; D. V. Sokolov; V. V. Bolotov (Омский научный вестник)
The composites based on manganese oxide (MnO2–х), copper oxide (CuO) and yttrium oxide (Y2 O3) are obtained. The gas response and selectivity of multicomponent composites to toxic and hazardous gases are found. Enhanced gas response of MnO2–х/CuO composite to hydrogen sulfide and methylcyan are observed as compared with as-grown manganese oxide. Doping of MnO2–x by yttrium oxide instead of copper oxide leads to changes gas-sensing properties of the composite to hydrogen sulfide, formaldehyde and sulfur dioxide. The presence of copper and yttrium oxides in MnO2–x increases the response to ethyl alcohol vapors.